A chiral 3D silver(i)–benzenedithiolate coordination polymer exhibiting photoemission and non-linear optical response. Issue 58 (29th June 2022) - Hawila, Saly; Abdallah, Ahmad; Rukemampunzi, Jean-Luc; Fateeva, Alexandra; Ledoux, Gilles; Debord, Régis; Paihlès, Stéphane; Guillou, Nathalie; Massuyeau, Florian; Gautier, Romain; Mesbah, Adel; Demessence, Aude
Abstract : A neutral coordination polymer made of Ag(i ) and 1, 3-benzenedithiolate, [Ag2 (1, 3-BDT)] n, displays both photoluminescence properties and a second harmonic generation signal. Abstract : A new tridimensional metal–organic chalcogenolate, made of a 1, 3-benzenedithiolate bridging ligand and Ag(i ), [Ag2 (1, 3-BDT)] n, is reported. This coordination polymer has good thermal stability in air and displays both photoluminescence properties and a second harmonic generation response.